Analisis Implementasi Ergonomi Kognitif Menggunakan Metode Situation Awareness Rating Technique Pada Pengemudi Bus Akap - Muhammad Ramdan; Siswiyanti Siswiyanti; Saufik Luthfianto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The high risk of traffic accidents driven by human error particularly fatigue associated with shift work can compromise driver alertness. This study aimed to analyze the implementation of cognitive ergonomics using the Situation Awareness Rating Technique (SART) among inter-city, inter-provincial (AKAP) bus drivers on the Purbalingga-Jakarta route, specifically examining differences in situation awareness levels between morning and night shifts. A descriptive quantitative approach was employed, involving 16 drivers divided into two shifts. The results indicated an average driver age of 35 years and an average work experience of two years across both shifts. An independent sample t-test yielded a significance value of 0.063, indicating no significant difference in situation awareness between the morning and night shifts, although the mean score for the night shift was slightly lower than that of the morning shift. Recommendations include managing rest schedules, conducting periodic health check-ups, and evaluating shift rotation practices.